An Overview: Feasibility of Earthworm Species for Organic Waste: Exploring the Feasibility of Earthworm Species for Sustainable Organic Waste Management (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Inadequate organic waste management can contribute to the spread of diseases and have negative impacts on the environment. Vermicomposting organic waste could have dual beneficial effects by generating an economically viable animal feed protein in the form of worm biomass, while alleviating the negative effects of poor organic waste management. In this study, a low-maintenance vermicomposting system was evaluated as manure and food waste management system for small-holder farmers. A vermicomposting system using the earthworm species Eudrilus eugeniae and treating cow manure and food waste was set up in Kampala, Uganda, and monitored for 172 days. The material degradation and protein production rates were evaluated after 63 days and at the end of the experiment. The material reduction was 45.9 and the waste-to-biomass conversion rate was 3.5 in the vermicomposting process on a total solids basis. A possible increase in the conversion rate could be achieved by increasing the frequency of worm harvesting. Vermicomposting was found to be a viable manure management method in small-scale urban animal agriculture the return of investment was calculated to be 280 for treating the manure of a 450 kg cow. The vermicompost was not sanitised, although hygiene quality could be improved by introducing a post-stabilisation step in which no fresh material is added. The value of the animal feed protein generated in the process can act as an incentive to improve current manure management strategies.